THE FINANCIAL MECHANISM FOR PROVIDING INVESTMENT LENDING TO THE ECONOMY OF UKRAINE WITH THE PARTICIPATION OF INTERNATIONAL FINANCIAL INSTITUTIONS - Pantielieieva Natalia; Mishchenko Svitlana; Pantielieieva Kseniia (Scientific Journal of Pedagogy and Economics, 2019)
In the article, based on the analysis of investment and credit activity of Ukraine in quantitative and qualitative indicators during 1993-2018, the main tendencies have been identified, and an estimation of the efficiency of investment lending to the economy of Ukraine with the participation of international financial institutions has been made; the conceptual basis, to which in its essential relationship the concepts of "investment", "credit", "investment credit", "investment lending" are included, has been clearly defined; the author’s position on understanding the concepts of "investment lending with the participation of international financial institutions" and "a financial mechanism of investment lending with the participation of international financial institutions" has been shown; the financial mechanism of investment lending with the participation of international financial institutions has been developed, its principles have been substantiated, its functional structure and characteristic features have been determined; risk management, improving the efficiency of state target programs implementation, and development of institutional infrastructure have been highlighted; practical recommendations aimed at increasing investment activity and investment efficiency of projects implemented by international financial institutions have been developed.